(untitled) - Littlejohn, Stephen W. (Belmont, CA., 2008)
THEORIES OF HUMAN COMMUNICATION is considered the seminal text in the field. Littlejohn and Foss present the range of communication theories currently available in the discipline, organizing them according to the scholarly traditions and contexts from which they emerge. Clear and accessible writing, charts that summarize the relationships among theories, and sections devoted to applications and implications help position theories within the discipline as a whole.
Keywords: Communication,Giao tiếp; Philosophy,Triết lý sống